2014
DOI: 10.5194/acp-14-6003-2014
|View full text |Cite
|
Sign up to set email alerts
|

Cloud condensation nucleus activity comparison of dry- and wet-generated mineral dust aerosol: the significance of soluble material

Abstract: Abstract. This study examines the interaction of clay mineral particles and water vapor for determining the conditions required for cloud droplet formation. Droplet formation conditions are investigated for two common clay minerals, illite and sodium-rich montmorillonite, and an industrially derived sample, Arizona Test Dust. Using wet and dry particle generation coupled to a differential mobility analyzer (DMA) and cloud condensation nuclei counter, the critical activation of the clay mineral particles as clo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 69 publications
3
62
0
Order By: Relevance
“…Again, this would change the surface charge distribution and potentially affect the ice-nucleating efficiency of illite particles. If wet particle generation (dispersion of aqueous suspension by means of a pressurized air atomizer) is used, the redistribution of cations between suspended particles may be an issue, as suggested by Garimella et al (2014) for the case of CCN experiments. Further studies of samples without modification or ageing after dry dispersion or wet suspension are needed to get a better idea of the method intercomparison.…”
Section: Effect Of Mineralogical Properties: Whichmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, this would change the surface charge distribution and potentially affect the ice-nucleating efficiency of illite particles. If wet particle generation (dispersion of aqueous suspension by means of a pressurized air atomizer) is used, the redistribution of cations between suspended particles may be an issue, as suggested by Garimella et al (2014) for the case of CCN experiments. Further studies of samples without modification or ageing after dry dispersion or wet suspension are needed to get a better idea of the method intercomparison.…”
Section: Effect Of Mineralogical Properties: Whichmentioning
confidence: 99%
“…More quantitative investigations of the acid processing of both reference and atmospherically relevant materials, and of acid processing's influence on their respective immersion mode ice nucleation efficiencies, are needed. Recently, re-partitioning of soluble components of both swelling and non-swelling clay minerals and their effect on cloud condensation nucleation activity was reported (Sullivan et al, 2010;Kumar et al, 2011;Garimella et al, 2014). To address a potential importance of this effect on the icenucleating activity of illite NX in the wet dispersion experiments, we have measured the concentration of cations released by the illite NX sample placed into deionized water as a function of time, as described in Sect.…”
Section: Effect Of Mineralogical Properties: Whichmentioning
confidence: 99%
“…Additionally, a new parameterization has also been shown that assumes surface area of the volcanic to be 10 times greater than the original parameterization to account for the high porosity of volcanic ash (dashed line). has been shown that wet generation techniques can affect the hygroscopicity and cloud droplet formation ability of mineral dust (Sullivan et al, 2010;Garimella et al, 2014). Thus, allowing the ash samples to shake in solution for at least 12 h prior to immersion freezing experiments could cause the dissolution/redistribution of active surface sites.…”
Section: Immersion Freezing Of Droplets Containing Na / Ca Feldsparmentioning
confidence: 99%
“…Jung et al (2013) reported a hygroscopicity parameter, κ, value of 0.02-0.03 for the accumulation mode particles at different altitudes including the MBL, east of Barbados during a pronounced mineral dust episode. Such low κ values close to 0.01 as for pure dust (Garimella et al, 2014;Petters and Kreidenweis, 2007) are indicative of an accumulation mode dominated by dust with only minor amounts of hygroscopic particulate matter (PM) present. Hence, mineral dust particles may play an important role as CCN under certain conditions over the North Atlantic.…”
Section: Introductionmentioning
confidence: 99%